Program improving autonomy and scientific research in remote education - Juana Venegas-Claros; Aracelli Gonzales-Sánchez; Luis Alex-Valenzuela; Joel Visurraga-Agüero; Carlos Augusto Luy-Montejo (Revista on line de Política e Gestão Educacional)
Students in Regular Basic Education have shown some difficulties in developing autonomy during their learning sessions; however, this situation increased when remote education was implemented, due to mandatory confinement, caused by the emergence of Covid 19, an alternative had to be sought, which allowed solutions to this situation to be provided. It was formulated as a study objective was to implement a Program improving autonomy and scientific research in remote education. The method used was a quantitative approach, with experimental design, a population of 84 students from the I.E. Celso Lino Ricaldi was used, a program was applied in ten sessions, resulting after its implementation, in the post test that 35.71% of the control group and 67.86% of the experimental group are at the level achieved. This data led to the conclusion that the programme implemented has positive effects on the autonomous learning and scientific research of the chosen educational institution.